Potensi Mineral Silika Pulau Rupat sebagai Proppant Alami Berdasarkan Kriteria API 19C - Novrianti; Rezi Indra; Dike Fitriansyah Putra; M. Ridha Fikri (BBPMGB LEMIGAS, 2025)
This study evaluates the suitability of silica sand from Rupat Island, Indonesia, as a natural proppant candidate for hydraulic fracturing applications, based on API RP19C specifications. The investigation involved three samples: unmodified silica sand, 5 % resin-coated sand, and 10 % resin-coated sand. Key properties assessed include roundness and sphericity, bulk density, turbidity, acid solubility, and crush resistance. The results show a significant improvement in roundness and sphericity with resin coating, with the 10 % coated sample reaching a value of 0.7—meeting the API minimum requirement of >0.6. All samples exhibited bulk density values exceeding the API minimum of 1.5 g/cc, specifically 1.53 g/cc, 1.58 g/cc, and 1.60 g/cc, respectively. Turbidity values were also low, ranging from 20 to 38 NTU, well below the API limit of 250 NTU. Acid solubility decreased with increasing resin fraction, from 2.8 % (uncoated) to 2 % and 1.2 %, all within the acceptable API limit of <3 %. In the crush resistance test using 40/70 mesh, all samples demonstrated acceptable levels of particle degradation: 6.7% at 2000 psi for uncoated sand, and 9 % and 8 % at 6000 psi for resin-coated samples—each remaining below the API maximum of 10 %. These findings suggest that Rupat Island silica sand, when modified with resin coating, holds strong potential as an alternative proppant for hydraulic fracturing operations.